EFFECTS OF DIFFERENT GUMS ON THE SOME PROPERTIES OF FRIED BEEF PATTIES - Kilincceker, Osman; Yilmaz, Mustafa Tahsin (NORTH UNIV CENTER BAIA MARE, 2016)
The aim of the study was to determine the effects of treatments with different gums on fried beef patties. Meat patties were prepared with three different formulations (0.5, 1 and 1.5%) for each of guar gum, xanthan gum, and gum Arabic. Some physical, chemical, and sensorial properties of fried samples were evaluated. As a result, guar gum and xanthan gam showed better effect on yield and diameter reduction. Gum Arabic increased L and b values of fried meat patties whereas guar more increased the moisture retention than others. However, gum Arabic had higher performance on the sensorial properties of beef patties. It was also observed that high levels of gums had much better results as an ingredient in fried patties compared with the other treatments. According to results, it was determined that especially 1.5% level of guar and all level of gum Arabic can be recommended for beef patties.
Keywords: Beef patty; guar gum; xanthan gum; gum Arabic; frying; FATTY-ACID-COMPOSITION; QUALITY CHARACTERISTICS; PHYSICOCHEMICAL PROPERTIES; SENSORY CHARACTERISTICS; BRAN ADDITION; FLOUR; CARRAGEENAN; COOKING; XANTHAN; STARCH; Food Science & Technology